Efficacy of feeding finishing-pigs to heavier weights on two protein sequences - B A Koch; G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1976)
Eighty-four pigs averaging 75 lbs. were used to evaluate feeding finishing hogs to 230, 260, or 290 lbs. on two protein regimes. Rate of gain declined after the pigs reached 200 lbs. regardless of protein level, which resulted in an increase of approximately 20 to 25 days required for each pen of pigs to average 30 lbs. of gain. Feed costs increased with the increased pounds of feed required per pound of gain for the heavier weights. Pigs fed the lower protein level from 200 lbs. to final weight required more feed per pound of gain, yielded carcasses with slightly more backfat thickness and significantly smaller loin eye areas than pigs fed more protein.; Swine Day, Manhattan, KS, November 11, 1976
Keywords: Swine day; 1976; Kansas Agricultural Experiment Station contribution; no. 519-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Finishing pigs; Protein; Loin eye area; Fat thickness